The lord of the rings the fellowship of the ring : visual companion - Fisher, Jude; Tolkien, J. R. R. 1892-1973. (Boston Houghton Mifflin, 2001)
The official authorized companion book to the Fellowship of the Ring, published to coincide with the release of the first part of Peter Jackson's epic film trilogy, The lord of the rings
Keywords: Tolkien, J. R. R. -- 1892-1973.; Middle Earth (Imaginary place); Fantasy fiction, English -- Movie Guide